In-depth understanding of soluble base deactivation during the carbonate transesterification process. (1st February 2021) - Yu, Yue; Shi, Lei; Guo, Jianjun; Li, Xin; Yang, Wenbing; Zhang, Zhigang; Xu, Guangwen
Highlights: The relationship among alkali strength, nucleophilicity and activity were established. A possible deactivation mechanism of soluble bases was proposed. The interaction between DMC and NaOH led to the formation of Na2 CO3 . Abstract: Soluble strong bases such as NaOH or CH3 ONa were industrially applied in production of multiple carbonates via the transesterification route. However, the catalytic efficiency decreased significantly after recycling and insoluble solids were formed, leading to a complicated and non-eco-friendly manufacture process. In this study, the influence of Na-based soluble basic catalysts (C4 H9 ONa, C2 H5 ONa, CH3 ONa, NaOH, Na2 CO3, and NaHCO3 ) structures, amounts, reusability, reaction atmospheres, and different reactants treatment were systematically studied for in-depth understanding the deactivated processes and mechanism. The results indicated dimethyl carbonate (DMC) was responsible for the deactivation and with decreasing the pKb (alkalinity coefficient) value, the alkali strength, nucleophilicity, and catalyst efficiency increased. The properties of fresh, DMC-treated and recycled NaOH or CH3 ONa samples were characterized by means of XRD, FT-IR, Raman, TG, and SEM. Nearly all the characterizations proved that the final deactivation species was Na2 CO3 after long-time treatment or recycle. A possible deactivation mechanism of soluble bases during the transesterification process was proposed. The presence of trace H2 O was the induction of CH3 ONa deactivation, whereas the interaction between DMC and NaOH led to the formation of Na2 CO3 . This finding will contribute to the development of strategies to design homogeneous catalysts with high activity and stability for carbonate transesterification.